Pengaruh Media Pembelajaran Interaktif Articulate Storyline 3 Terhadap Kemampuan Berpikir Historis Siswa di Kelas XII SMA Negeri 4 Pandeglang - Neng Mutiah; Rikza Fauzan; Arif Permana Putra (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to determine the effect of Articulate Storyline 3 interactive learning media on the historical thinking ability of class XII students in History subject at SMA Negeri 4 Pandeglang. The research method used in this research is quasi-experiment. Data collection was carried out through purposive sample technique with class XII-5 as many as 40 students as an experimental class using Articulate Storyline 3 interactive learning media and class XII-1 as many as 40 students as a control class using YouTube video learning media. The results of the study are as follows; there is an effect of Articulate Storyline 3 interactive learning media on students' historical thinking ability, hypothesis testing through a two-party t-test there is an increase in students' historical thinking ability by obtaining a Sig. (2-tailed) of 0.000 < 0.05 then Ha is accepted and H0 is rejected, which means there is an increase in students' historical thinking ability in class XII history subjects at SMA Negeri 4 Pandeglang after using Articulate Storyline interactive learning media. Basically, the Articulate Storyline 3 application can be used as a recommendation as a digital learning media that serves to determine the level of student understanding of learning material, especially in history subjects which has the aim of one of which is to develop students' historical thinking skills.